PROMOTING SUSTAINABLE DEVELOPMENT: A HOLISTIC APPROACH TOWARDS A RESILIENT FUTURE - Ishfaq Ahmad Mir (PT. Radja Intercontinental Publishing, 2023)
Sustainable development has emerged as a global imperative to address the pressing challenges of environmental degradation, social inequality, and economic instability. This research paper explores the concept of sustainable development, its key principles, and the critical role it plays in shaping a resilient and prosperous future. It investigates the interconnectedness between environmental, social, and economic dimensions, highlighting the need for an integrated approach. Furthermore, the paper examines various strategies and initiatives that promote sustainable development at local, national, and international levels. It also discusses the challenges and barriers to achieving sustainable development and presents potential solutions for overcoming them. By presenting a comprehensive analysis, this paper contributes to the ongoing discourse on sustainable development and offers insights into its implementation across different sectors and regions.